Barium molybdate and barium tungstate nanocrystals synthesized by a cyclic microwave irradiation - Anukorn Phuruangrat (2018)
BaMoO4and BaWO4nanocrystals were synthesized from Ba(NO3)2and Na2MeO4(Me=Mo and W) solutions using 50% of 600 W microwave irradiation for 20 min. The products were characterized using X-ray diffraction (XRD), Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), selected area electron diffraction (SAED) and photoluminescence (PL) spectrophotometry. They show that the products are good dispersed nanocrystals (poly-nanocrystals) of single-phase scheelite tetragonal structure with the vibration modes corresponding to the molybdate and tungstate compounds. Their photoluminescence was detected at 415 and 392 nm for BaMoO4and BaWO4, respectively. © 2009 Elsevier Ltd. All rights reserved.